Application of General Circulation Models to Assess the Potential Impact of Climate Change on Potential Distribution and Relative Abundance of Melanoplus sanguinipes (Fabricius) (Orthoptera: Acrididae) in North America - O. Olfert; R. M. Weiss; D. Kriticos (Psyche: A Journal of Entomology)
Climate is the dominant factor determining the distribution and abundance of most insect species. In recent years, the issue of climatic changes caused by human activities and the effects on agriculture has raised concern. General circulation model scenarios were applied to a bioclimatic model of Melanoplus sanguinipes to assess the potential impact of global warming on its distribution and relative abundance. Native to North America and widely distributed, M. sanguinipes is one of the grasshopper species of the continent most responsible for economic damage to grain, oilseed, pulse, and forage crops. Compared to predicted range and distribution under current climate conditions, model results indicated that M. sanguinipes would have increased range and relative abundance under the three general circulation model scenarios in more northern regions of North America. Conversely, model output predicted that the range of this crop pest could contract in regions where climate conditions became limiting.